MO345: Clinical Characteristics and Trajectory in a National Cohort of Veterans Treated With Conservative Management Versus Dialysis. (3rd May 2022) - Narasaki, Yoko; Rhee, Connie; You, Amy; Mukamel, Dana; Novoa, Alejandra; Otobe, Yuhei; Daza, Andrea; Kovesdy, Csaba; Crowley, Susan; Nguyen, Danh; Kalantar-Zadeh, Kamyar
Abstract: BACKGROUND AND AIMS: Within the Veterans Health Administration, the largest integrated healthcare system in the USA, 1.1 million Veterans (16.4%) have been identified as having chronic kidney disease (CKD). Annual spending on US Veterans with non-dialysis dependent CKD is estimated at 19 billion/year, and each year ∼10% of US Veterans with advanced CKD progress to end-stage renal disease (ESRD) requiring renal replacement therapy in the form of dialysis or kidney transplantation. While dialysis has been the dominant treatment paradigm in this population, with ∼22 000 enrolled Veterans receiving dialysis from VA-based dialysis facilities or from VA-contracted community providers, this treatment approach may not offer survival benefit nor improved quality of life in certain subgroups (elderly, multi-morbid). We sought to examine the clinical characteristics of a contemporary cohort of US Veterans with advanced CKD treated with conservative non-dialytic management versus dialysis. METHOD: In a national cohort of US Veterans receiving care from the VA healthcare system, we identified patients with advanced CKD, identified as those with ≥ 2 eGFR measurements < 25 mL/min/1.73 m 2 separated by ≥ 90 days over the period of 1 October 2010–30 September 2019. Used linked United States Renal Data System and Medicare data, patients were categorized according to (1) receipt of conservative management (CM), defined as those who did not receive dialysis within 2 years of the index eGFR (first eGFR < 25 mL/min/1.73 m 2 ) and (2) receipt of dialysis within 2 years of the index eGFR. We then examined the clinical characteristics and outcome trajectory of those treated with CM versus dialysis, with follow-up through 30 September 2021. RESULTS: Among 106 089 advanced CKD patients who met eligibility criteria, 24.6% ( N = 26 113) and 75.4% ( N = 79 956) were treated with dialysis versus CM, respectively (index eGFR distribution shown in Fig. 1, left panel). In the overall cohort, the mean ± SD age was 73 ± 12 years and 97.4% were men, with a younger age distribution seen in those receiving dialysis versus CM, yet a similar sex distribution across the two treatment groups (Table 1). Across racial groups, there was a greater tendency for Black, Asian, Pacific Islander and Native American Veterans to undergo dialysis versus CM as compared with Veterans of White race. A greater proportion of deaths were observed among Veterans treated with dialysis versus CM (73.2% versus 70.3%, respectively; available follow-up time to censoring or death is shown in Fig. 1, right panel). CONCLUSION: In a nationally representative CKD cohort, we observed differences in socio-demographics, including racial background, among patients who were treated with CM versus dialysis. Additionally, death was more frequently observed in those who underwent dialysis versus CM. Further studies are needed to examine the comparative effectiveness of CM versus dialysis transition on CKD outcomes.